2008
DOI: 10.1111/j.1440-1681.2008.04923.x
|View full text |Cite
|
Sign up to set email alerts
|

DEFECTIVE INTRACELLULAR Ca2+ HOMEOSTASIS CONTRIBUTES TO MYOCYTE DYSFUNCTION DURING VENTRICULAR REMODELLING INDUCED BY CHRONIC VOLUME OVERLOAD IN RATS

Abstract: 1. Previous studies have demonstrated progressive ventricular hypertrophy, dilatation and contractile depression in response to chronic volume overload. Whether this decompensation was related to intrinsic myocyte dysfunction was not clear. The present study evaluated ventricular myocyte function at critical times during the progression of ventricular remodelling induced by volume overload. 2. Chronic volume overload was induced with an infrarenal aortocaval fistula in rats. Myocyte contraction and intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 46 publications
0
25
1
1
Order By: Relevance
“…Allopurinol has also been shown to improve Ca 2ϩ homeostasis and oxidation/nitration of Ca 2ϩ -handling proteins in the tachypacing model in the dog (34) and in the spontaneously hypertensive rat (19). In the present study, there was no change in SERCA protein levels and that of its regulator, PLN, at 8 wk, whereas 12-wk ACF has been reported to have a decrease in SERCA2 expression associated with decreased LV contractility and the response to Ca 2ϩ infusion in the isolated ACF heart (13,36). It is of interest that we found an increase in SLN in ACF LVs that was decreased by allopurinol.…”
Section: Discussioncontrasting
confidence: 40%
“…Allopurinol has also been shown to improve Ca 2ϩ homeostasis and oxidation/nitration of Ca 2ϩ -handling proteins in the tachypacing model in the dog (34) and in the spontaneously hypertensive rat (19). In the present study, there was no change in SERCA protein levels and that of its regulator, PLN, at 8 wk, whereas 12-wk ACF has been reported to have a decrease in SERCA2 expression associated with decreased LV contractility and the response to Ca 2ϩ infusion in the isolated ACF heart (13,36). It is of interest that we found an increase in SLN in ACF LVs that was decreased by allopurinol.…”
Section: Discussioncontrasting
confidence: 40%
“…The modest elevation in maximum dP/dt observed in compensated and decompensated animals could be related to elevated neurohormonal input from chronic sympathetic stimulation and increased levels of circulating epinephrine/norepinephrine. A recent study by Ding et al (18) demonstrated that isolated myocytes from hearts 5 wk postfistula were still responsive to adrenergic stimulation. However, isolated myocytes from hearts 10 wk postfistula were unresponsive (lacking a response) to the same adrenergic challenge (18).…”
Section: Effect Of Et a Receptor Antagonism On Postfistula Remodelingmentioning
confidence: 99%
“…A recent study by Ding et al (18) demonstrated that isolated myocytes from hearts 5 wk postfistula were still responsive to adrenergic stimulation. However, isolated myocytes from hearts 10 wk postfistula were unresponsive (lacking a response) to the same adrenergic challenge (18). Regardless, the extent of chamber dilatation present in the decompensated group in conjunction with the depressed stroke volume, cardiac output, and ejection fraction are indicative of a heart that is beginning to fail.…”
Section: Effect Of Et a Receptor Antagonism On Postfistula Remodelingmentioning
confidence: 99%
“…Heart failure occurred subsequently between 8 to 16 weeks with depressed in vivo and in vitro LV systolic pressure. Previous study from our laboratory indicates that depressed ventricular contractility is intrinsic to the individual myocytes [7] . In that study the in vivo cardiac size and performance following fistula surgery was evaluated by M-mode echocardiography.…”
Section: Introductionmentioning
confidence: 92%